Bilateral caudal maxillectomy for resection of tumors crossing palatal midline and use of the angularis oris axial pattern flap for primary closure or dehiscence repair in two dogs. Issue 8 (10th June 2019) - Tuohy, Joanne L.; Worley, Deanna R.; Wustefeld‐Janssens, Brandan G.; Mickelson, Megan A.; Ehrhart, Nicole P.; Seguin, Bernard
Abstract: Objective: To describe the technique and outcomes for bilateral caudal maxillectomy for resection of large caudal maxillary tumors crossing palatal midline in two dogs. Study design: Clinical case report. Animals: Two client‐owned dogs. Methods: Two client‐owned dogs with primary caudal maxillary tumors, a poorly differentiated sarcoma, and a multilobulated osteochondrosarcoma. Bilateral caudal maxillectomies were performed for curative‐intent resection of these tumors. The angularis oris axial pattern flap was used for primary closure in one dog and for dehiscence repair in the other. Results: Both tumors were resected with complete histologic margins. The defects were closed with local buccal mucosal flaps, with or without a unilateral angularis oris flap. Esophagostomy tubes were placed at time of surgery to bypass oral feeding. Incisional dehiscence and subsequent oronasal fistula formation occurred as a postoperative complication in both dogs (3 and 10 days, respectively). Both were successfully repaired with a combination of local buccal mucosal flaps and the angularis oris flap. Both dogs had good functional outcome and quality of life after recovery from revision surgery. Conclusion: Bilateral caudal maxillectomy allowed resection of caudal maxillary tumors crossing palatal midline, with good function and quality of life after recovery in 2 dogs. Clinical significance: Good outcomes including complete resections are achievable with bilateral caudal maxillectomy despite complications. Local mucosal and axial pattern flaps can be used for dehiscence repair.